1973
DOI: 10.1111/j.1095-8649.1973.tb04456.x
|View full text |Cite
|
Sign up to set email alerts
|

Overwinter feeding in rainbow trout

Abstract: The contents of the stomachs of 38 rainbow trout stocked in Llyn Alaw, Anglesey, in August 1969 and caught between October 1969 and February 1970 were analysed. The fish were actively feeding on the bottom fauna throughout the winter and 21 of the stomachs were full or distended. The mean volume of the contents of the stomachs was 2–8 times greater than that of the contents of stomachs of similarly sized brown trout caught at the same time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

1982
1982
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…The value for rainbow trout was higher than most reported studies, e.g. 0% (Hunt & O'Hara 1973), and may have been a result of samples containing recently introduced, naive stock fish which had not yet begun to eat natural food. In Winkworth, during the summer months there is evidence that both species can be stocked at densities of 50-100 fish/ha with little likelihood of competition since there is little niche overlap.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…The value for rainbow trout was higher than most reported studies, e.g. 0% (Hunt & O'Hara 1973), and may have been a result of samples containing recently introduced, naive stock fish which had not yet begun to eat natural food. In Winkworth, during the summer months there is evidence that both species can be stocked at densities of 50-100 fish/ha with little likelihood of competition since there is little niche overlap.…”
Section: Discussioncontrasting
confidence: 62%
“…2 this was due largely to similar benthic feeding habits. Hunt & O'Hara (1973) found rainbow trout sampled in winter to be feeding on bottom fauna, and it appears that at lower water temperatures rainbow trout may adopt a benthic feeding strategy, perhaps because planktonic food is scarce. Under these circumstances, rainbow trout may be competing with brown trout for food.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is a common belief that brown trout generally feed at greater depths than rainbows but both species take aerial insects and bottom fauna . Little work has been published on the feeding of brown and rainbow trout in the same environment but that of Hunt & Jones (1972) and Hunt & O'Hara (1973) support these statements . The first trout introduced were 1+ brown trout ranging between 5 g and 45 g but the remaining fish released in 1975 were all 0+ fish weighing less than 20 g .…”
Section: Initial Introductions Of Troutmentioning
confidence: 75%
“…waters is usually believed to be associated with failure to release ova but Hunt & O'Hara (1973) suggested that rainbows adopted a bottom feeding behaviour following autumn stocking and were therefore more difficult to catch . Cragg-Hine (1975) recorded low angling catch of autumn stocked immature rainbow trout in Northern Ireland lakes and concluded poor survival was related to the presence of other trout although there was no evidence of cannibalism .…”
Section: Survival Of Brown and Rainbow Troutmentioning
confidence: 99%